ENT530: Al-Haqq Imani / Amirrul Asyraf Ahmad Rafaei, Mohamad Alias Zakaria and Naimuddin Ahmad Saberi - Ahmad Rafaei, Amirrul Asyraf; Zakaria, Mohamad Alias; Ahmad Saberi, Naimuddin (2017)
Al-Haqq Imani is the company which control the activity of disposal of Al-Qur'an and other reading material. The company is focuses on producing quality service. We choose this business because we believe that it will create a new lifestyle and people will interested with our service. Plus we are promoting a quality service which will satisfy the customers' impression. The establishment of this company is to inform people how to dispose Al-Qur'an in the right way. Our main purposes to make this service is well known, attract the teenagers to involve and create the good relationship between competitors. The truly intention that we create this business is only to gain 'pahala' from Allah S.W.T. It is more to the charity sector. As long as we can do our best to protect the holiness of Al-Qur'an. Our company consist five partnership like administration, marketing, financial, and two person operations supervisor. For the information, our company's operation hour is started at 9.00 a.m. until 5.00 p.m. on Monday until Saturday. Besides that, our company is located at Shah Alam, Selangor.